x*3+142=x*13-8

Simple and best practice solution for x*3+142=x*13-8 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x*3+142=x*13-8 equation:


Simplifying
x * 3 + 142 = x * 13 + -8

Reorder the terms for easier multiplication:
3x + 142 = x * 13 + -8

Reorder the terms:
142 + 3x = x * 13 + -8

Reorder the terms for easier multiplication:
142 + 3x = 13x + -8

Reorder the terms:
142 + 3x = -8 + 13x

Solving
142 + 3x = -8 + 13x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-13x' to each side of the equation.
142 + 3x + -13x = -8 + 13x + -13x

Combine like terms: 3x + -13x = -10x
142 + -10x = -8 + 13x + -13x

Combine like terms: 13x + -13x = 0
142 + -10x = -8 + 0
142 + -10x = -8

Add '-142' to each side of the equation.
142 + -142 + -10x = -8 + -142

Combine like terms: 142 + -142 = 0
0 + -10x = -8 + -142
-10x = -8 + -142

Combine like terms: -8 + -142 = -150
-10x = -150

Divide each side by '-10'.
x = 15

Simplifying
x = 15

See similar equations:

| 2cosx=-3insx | | 5/9=10/k-12 | | 5/9=10/k-2 | | 2(3-2n)=-(n+5) | | P^2-10+c=0 | | 2y=6+4 | | (3x+30)(3x+3)-(2x-1)(2x-1)=0 | | -4-1-1= | | 5(h+2)+3(h+4)=78 | | 3y=5(v-4) | | -2+5-3= | | 9+3x=6-(2x) | | (3x-30)(3x+3)-(2x-1)(2x-1)=0 | | T=C(9+AB)forB | | 2128.88=2100.00(1+0.25) | | 5y^2+8y=13 | | cos(4x)-cos(2x)+sin(3x)=0 | | 2x-3-1= | | (3x-30)(3x+3)-(2x-1)*2=0 | | 5x-57-2x= | | X^4-3x^3+x^2-3x+3=0 | | 35/20=n/4 | | 10=-7x-x^2 | | 4x+-5=7x-3 | | -(6v-2x-1)= | | -2-3-1= | | 270=0.5x^2+36x-40 | | 5-4-4= | | (2x+3)(x-6)-(5x+3)(3x+4)= | | 9r^2-5=76 | | ×/5=7.5 | | 4y+12=7y+36 |

Equations solver categories